Persepsi Etika Penggelapan Pajak: Pengaruh Langsung dan Tidak Langsung - Dewi Sofha; Zaky Machmuddah (Akuntabilitas, 2019)
Tax evasion could be seen as ethical deed or not depends on several factors. The goal of this research is to examine the influence of gender, religiosity, and love of money towards tax evasion ethical perspective. The population of this research is undergraduate (S1) accounting students from private universities in Semarang. The sample used in this research covers final semester the undergraduate (S1) accounting students from University of Dian Nuswantoro, University of Soegijapranata Catholic, University of Sultan Agung Islamic, University of Muhammadiyah Semarang, University of Stikubank, University of Wahid Hasyim and University of AKI. The sampling technique used in this research is accidental sampling. As much as 100 questionnaires have been spread to the chosen respondents and all of them are declared proper to use. The analysis result is gender and religiosity do have impact on tax evasion ethical perspective while love of money does not. This research’s result also shows that religiosity and love of money do not mediate the relationship between gender and tax evasion ethicalperspective.